Fiscal Policy to Encourage Investment in the Marine Logistics Sector - Wihdat Djafar (Collaborate, 2024)
The marine logistics sector plays a crucial role in a country's economic growth, particularly for archipelagic nations like Indonesia. However, investment levels in this sector remain low, which can hinder potential economic growth. This research aims to analyze various fiscal policies that can encourage investment in the marine logistics sector. The methods used in this research are qualitative and quantitative descriptive analysis. The results indicate that fiscal policies such as tax incentives, subsidies, and government funds allocated for maritime infrastructure development can increase the attractiveness of investment in this sector. Tax incentives, such as reductions in corporate income tax rates, exemptions or reductions in import taxes for equipment, and tax allowance facilities, can be effective instruments to attract investment. Subsidies, such as capital assistance, low-interest loans, and operational cost compensation, can also help reduce investment risks and encourage investor participation. Additionally, adequate allocation of government funds for the development of maritime infrastructure, such as ports, docks, and other logistics facilities, is crucial for enhancing the sector's efficiency and competitiveness. However, fiscal policies alone are not enough. Improved regulations and better law enforcement are also necessary to create a conducive investment climate in the marine logistics sector.